Hippocampal Volume Predicts Conversion to Dementia in Patients with Mild Cognitive Impairment - Canavan, Neil (MD Conference Express, 2008)
In a study that had a 5-year follow-up, hippocampal volume (HV) was shown to be correlated with elevated risk in a cohort of elderly patients with mild cognitive impairment. Individuals who developed dementia had a smaller HV at baseline.